Echinostelium microsporum (Echinosteliaceae, Myxomycetes), a new epiphytic corticolous species from Russia - Vlasenko, Anastasia V.; Filippova, Nina V.; Vlasenko, Vyacheslav A. (Phytotaxa, 2019)
A new species, Echinostelium microsporum, is described and illustrated herein. Samples of this species were collected in the Khanty-Mansi Autonomous Area—Yugra, Russia. It clearly differs from the previously known species in form and structure of columella, number of capillitial threads, their development and branching, and size of spores. Columella of E. microsporum is sponge-like and with deep dark-brown indentations. Its capillitium always extend from three areas at the side of the columella. Capillitial threads are long and always numbering 3, dichotomous and branching into two parts at the ends. Spore-like body is absent. Spores are small, warted and with walls of uniform thickness. We present here a scanning electron micrograph study of E. microsporum and an updated identification key for species of the genus Echinostelium worldwide, which currently includes 16 taxa. A holotype specimen of E. microsporum is deposited in M.G. Popov Herbarium (NSK). It is the second new species for the genus discovered in Russia, with type locality in Siberia, Northern Asia.